PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PERJUDIAN MELALUI AJANG BALAP LARI DI KUTAI KARTANEGARA - Septiawan, Aristo; Sabaruddin, Abdul Kadir; Apriyani, Rini (Media Inovasi Pendidikan dan Publikasi, 2025)
This study examines law enforcement efforts against gambling offenses occurring during seasonal running races in Kutai Kartanegara Regency, particularly during the month of Ramadan. This phenomenon is often used by the community as a means of gambling, even though it is presented as a recreational and sporting event. The study employs a socio-legal method with a qualitative approach. The results show that although legal provisions clearly prohibit gambling under Article 303 of the Criminal Code and Article 15 of the Police Law, implementation remains suboptimal. The police do not possess official data on gambling in these events, despite empirical evidence from local communities. The main obstacles include a lack of public reports, weak field supervision, and limited proactive measures by law enforcement officers. The study emphasizes the need for improved coordination, consistent monitoring, and preventive legal education to enhance the effectiveness of law enforcement.